2014
DOI: 10.1177/1420326x14536749
|View full text |Cite
|
Sign up to set email alerts
|

Indoor radon in dwellings of Jeddah city, Saudi Arabia and its correlations with the radium and radon exhalation rates from soil

Abstract: To assess the potential health risks associated with indoor radon, a study was carried out in 80 dwellings in Jeddah city, Saudi Arabia using CR-39 plastic track detectors. The annual average indoor radon concentrations varied from 21 to 52 Bq m−3, with a mean value of 36 Bq m−3, which is well below the recommended action level recommended by the International Commission on Radiological Protection (ICRP). The annual effective dose varied from 0.35 to 0.89 mSv y−1. The results showed no significant radiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 35 publications
2
10
3
Order By: Relevance
“…For more safety the workers advised to improve ventilation; since it is well known that an increased ventilation rate is an important factor in reducing the indoor radon level [41]. We also found that the radon concentrations in moderately ventilated health centers were relatively higher when compared to those in well-ventilated ones.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…For more safety the workers advised to improve ventilation; since it is well known that an increased ventilation rate is an important factor in reducing the indoor radon level [41]. We also found that the radon concentrations in moderately ventilated health centers were relatively higher when compared to those in well-ventilated ones.…”
Section: Resultssupporting
confidence: 57%
“…Our average values obtained here is lower than that reported values from Omdurman and Sinnar, Sudan [16], Brazil [47], Iraq [49], and Pakistan [50], higher than the recorded values for Jordan [13], Saudi Arabia [41] and India [46], nearer to the values reported from Al-Hosh (Sudan) [16 ] and USA [44]. …”
Section: Resultscontrasting
confidence: 55%
“…Having close observation at Table 2 which compares values from different regions in Sudan and other Countries, the average values of radium concentration and radon exhalation rates (surface and mass) obtained here is lower than that reported from Saudi Arabia [7], Singa and Rabak towns, Sudan [15], Ethiopia [34], higher than the recorded values for Bulandshahr district, Uttar Pradesh-India [35], Egyp [36], Karbi Anglong district of Assam-India [37] and nearer to the values reported from India [38].…”
Section: Resultsmentioning
confidence: 57%
“…The inhalation of radon and its daughter products can cause a significant health hazard when present in enhanced levels in the enclosed indoor environments like a human dwelling [1 -6]. The radon concentration in the ground depends on the radium content of the soil and the emanation power of soils and rocks [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Radon is produced due to the radioactive decay of radium in earth crust. It's concentration in the ground depends on the radium content of the soil and the emanation power of soils and rocks [5], [6]. Radium is a decay product of uranium in the naturally occurring uranium series.…”
Section: Contribution Of Indoor Radon (mentioning
confidence: 99%